Dr. Carlos Alberto Soto Medina — Deep Plane Facelift — Ciudad Juárez - Soto Medina, Carlos Alberto (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Carlos Alberto Soto Medina, practicing in Ciudad Juárez, Mexico. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003186; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; mexico; ciudad juárez